Estimating the economic impact of a one‐time event: The case of l'Hermione in Yorktown. Issue 4 (19th February 2021) - Hall, Thomas; Shuck, Sheri M.
Abstract: In an era of pressure on government resources, nonprofits can serve an important role in the provision of services to the public. However, without clear and quantifiable estimates of their impact, it is difficult for policymakers to justify allocating governmental resources toward these services. This is especially the case for ephemeral opportunities that arise without substantial advance notice or a special program that occurs only once (contrasted to programs that nonprofits provide on a continuing basis). This research note presents economic impact estimates for a unique example of a remarkable effort involving numerous entities from the government, for‐profit, and nonprofit sectors. Our contribution is to exemplify methods that might be used to assess the economic impact of ephemeral or one‐time events. Of course, each situation is unique, so the judgment of the analyst is always a key input. Using three survey‐generated data points per respondent, nonprofits can replicate the methods of this study to assess the economic impact of special events herein. With estimates such as the ones examined herein, policymakers can contrast the benefits of special events with their costs in order to determine if such events are worthwhile investments.